Metastatic seminoma presenting in an external iliac lymph node in an asymptomatic elderly patient undergoing screening in a multi-cancer early detection study: Report of a case and review of the literature - Benjamin F. Smith; Brenden L. Scott; Paul J. Michaels (Human Pathology Reports)
Multi-cancer early detection assays are being increasingly studied as a way to efficiently and effectively screen for low-stage and treatable cancers from various tissue origins with a single blood test. However, many of these tests suffer from a low positive predictive value and, in positive cases, may suggest tumor origin from a tissue site that is ultimately found to be inaccurate. This can lead to an expensive and often unnecessary diagnostic work-up. Seminomas of the testicle are poorly represented in the studies that have been done, as most of the studies enroll patients over the age of 50, a demographic with a very low incidence of germ cell tumors.Here, we report a case of a 67-year-old male who was found to have a “positive” cancer signal on the multi-cancer early detection assay used in the PATHFINDER-2 trial. An ensuing work-up showed an enlarged external iliac lymph node that was hypermetabolic on whole-body PET CT scan. A core biopsy was diagnostic of seminoma. Further evaluation and surgery revealed an ipsilateral regressed germ cell tumor of the testicle and evidence of additional non-regional lymph node metastases.